Analysis of 2′-hydroxyflavanone (2HF) in mouse whole blood by HPLC–MS/MS for the determination of pharmacokinetic parameters - Gervazoni, Luiza F. O.; Gonçalves-Ozorio, Gabriella; Ferreira-Paes, Taiana; Silva, Aline C. A.; Silveira, Gabriel P. E.; Pereira, Heliana M.; Pinto, Douglas P.; Cunha-Junior, Edézio F.; Almeida-Amaral, Elmo E. (Frontiers in Chemistry, 2023)
Given the lack of investment and structure and the difficulty of metabolite isolation, promising natural product studies do not progress to preclinical studies, such as pharmacokinetics. 2’-Hydroxyflavanone (2HF) is a flavonoid that has shown promising results against different types of cancer and leishmaniasis. Herein, an HPLC–MS/MS method was developed and validated to accurately quantify the content of 2HF in BALB/c mouse blood. Chromatographic analysis was performed using a C18 column (5 μm, 150 × 4.6 mm). The mobile phase consisted of water (containing 0.1% formic acid), acetonitrile, and methanol (35/52/13 v/v/v) at a flow rate of 0.8 mL/min and total run time of 5.50 min with an injection volume of 20 µL. 2HF was detected by electrospray ionization in negative mode (ESI-) using MRM. The validated bioanalytical method showed satisfactory selectivity without significant interference with 2HF and the IS. In addition, good linearity (r=0.9969) was observed in the concentration range of 1 and 250 ng/mL. Moreover, the method showed satisfactory matrix effect results. The precision and accuracy intervals varied between 1.89 and 6.76% and 95.27 and 100.77%, respectively, fitting the approval criteria. No degradation of 2HF in the biological matrix was observed, since its stability after freeze–thaw cycles, short-term storage, postprocessing, and long-term storage showed deviations of less than 15%. Once validated, the method was successfully applied in an oral pharmacokinetic study with mouse blood, and the pharmacokinetic parameters of 2HF were determined. 2HF demonstrated a Cmax of 185.86 ng/mL, a Tmax of 5 min, and a half-life (t1/2) of 97.52 min.